Estrategias de motivación para mejorar la comunicación oral en inglés en estudiantes de primer grado de secundaria en la institución educativa pública inicial primaria secundaria de menores 601486 Alexander Von Humboldt de Punchana 2023 - Olortegui Alva, Lizeth Nancy (2025)
The main purpose of this research was to assess the effectiveness of an educational program focused on motivational strategies aimed at promoting significant improvements in oral communication skills in English. This study was conducted with first-year secondary students from the Alexander Von Humboldt public school in Punchana, 2023. This study employed an evaluative research framework, incorporating field-based, contemporary cross-sectional, univariate, and quasi experimental designs. The study population consisted of 46 students, with a non probabilistic sample divided into two groups: an experimental group of 25 students and a control group of 21 students. The results obtained from the post-test showed that the average scores in oral communication in English were significantly higher in the experimental group compared to the control group, with values of 12.267 ˃ 10.156, respectively. These findings lead to the conclusion that the implementation of the educational program based on motivational strategies had a positive and statistically significant impact on improving the oral communication skills in English of the study population. This result led to the acceptance of the working hypothesis, as the obtained (p-value = 0.000) was smaller than the established significance level (α = 0.05).